Longitudinal structures in Mars' upper atmosphere as observed by MAVEN/NGIMS. Issue 1 (26th January 2017) - Liu, Guiping; England, Scott; Lillis, Robert J.; Mahaffy, Paul R.; Elrod, Meredith; Benna, Mehdi; Jakosky, Bruce
Abstract: Here we report the first comprehensive study of longitudinal structures in Mars' neutral upper atmosphere associated with atmospheric tides in composition, density and temperature using the Mars Atmosphere and Volatile Evolution Mission/Neutral Gas Ion Mass Spectrometer observations during 2015. These are in situ measurements of number densities of atmospheric species (including CO2, Ar, N2, and CO) in the altitude range from 120 to 200 km above the areoid (corresponding to a total density range from 10 8 –10 11 cm −3 ), providing a data set that is larger than all previous measurements of these waves combined. These observations span from ±70° latitude and cover a wide range of local times and solar longitudes (Ls), allowing for the study of longitudinal structures under various conditions. Furthermore, the data in May and November 2015 are at similar latitudes and local times but different Ls ( 340° in May, close to northern spring equinox, and 70° in November, close to northern summer solstice and aphelion), ideal for studying the seasonal effects of tides. Our analysis shows that in each month the Ar density varies with longitude having a large wave structure. It is dominated by wave 2 and 3, accounting for 8–16% of the change of the mean density. Comparison shows that the longitudinal structures at a constant CO2 density level have different amplitudes at different seasons, although their patterns are similar. The temperature structure has a phase difference from the density variation, indicating the dissipation of tides in this altitude region. The longitudinal structure is seen in all species, including major and minor species, consistent with the tidal signatures. Key Points: First comprehensive study of longitudinal structures in Mars' upper atmosphere associated with atmospheric tides using NGIMS data in 2015 First time that we are able to separate the seasonal effect of tides in the thermosphere from the local time and latitude variations Longitudinal tidal structures dominated by wave‐2 and 3 are seen in upper atmosphere density, temperature and composition